Farming system effects on biologically mediated plant–soil feedbacks. Issue 1 (31st January 2020) - Menalled, Uriel D.; Seipel, Tim; Menalled, Fabian D.
Abstract: Cropping system characteristics such as tillage intensity, crop identity, crop-livestock integration and the application of off-farm synthetic inputs influence weed abundance, plant community composition and crop-weed competition. The resulting plant community, in turn, has species-specific effects on soil microbial communities which can impact the growth and competitive ability of subsequent plants, completing a plant–soil feedback (PSF) loop. Farming systems that minimize the negative impacts of PSFs on subsequent crop growth can increase the sustainability of the farming enterprise. This study sought to assess the individual and combined impact of the cropping system (certified organic-grazed, certified organic till and conventional no-till) and crop sequence [pairwise rotations with safflower ( Carthamus tinctorius ), yellow sweet clover ( Melilotus officinalis ) and winter wheat ( Triticum aestivum )] on the PSF magnitude and direction. All cropping systems followed the same 5-year rotation and had completed one full rotation before soil was sampled. In a greenhouse setting, a sterile soil mix was inoculated with field soil collected from all systems and three crops. The PSF study consisted of two stages (conditioning and response phases) that mimicked the rotation stages occurring in the field. PSFs were calculated by comparing the biomass of the response phase plants grown in inoculated and uninoculated soils. The farm management system affected PSFs, inferring that tillage reduction can encourage more positive PSFs. Crop sequence did not affect PSF but interacted strongly with the farm system. As such, the effects of the farming system on PSFs are best illustrated when taken into account with the identity of the previous and current crops of a cropping sequence.